Uji Durabilitas Beton Normal Setelah Perendaman dalam Air Laut dan Pembakaran pada Suhu Tinggi - Arjuna, Sandika (Civil Infrastructure Engineering and Architectural Design, 2025)
This study aims to test the durability of normal concrete after exposure to a combination of two extreme conditions: immersion in seawater and burning at high temperatures (300°C, 400°C, and 500°C). The study is motivated by the vulnerability of structures in coastal areas to both aggressive chloride attacks and fire hazards. The concrete used was designed for 25 MPa compressive strength and tested at 28 days of age. Cylindrical specimens (15 cm diameter and 30 cm height) were immersed in seawater for 28 days, then burned in a drum furnace for 30 minutes at the specified temperatures. Testing included compressive strength, density, and porosity measurements. Results show significant deterioration at 500°C, moderate deterioration at 400°C, and minor deterioration at 300°C. This confirms the need for better durability strategies for concrete in extreme environments.